Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Escalating threats: house mouse attacks on adult wandering albatrosses spread across Marion Island - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Rhiannon Gill; Vanessa Stephen; Susan J. Cunningham; Peter G. Ryan (Biological Invasions, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Identification of novel microcystins in algal extracts by a liquid chromatography–high-resolution mass spectrometry data analysis pipeline - Kirsten A. Cottrill; Christopher O. Miles; Logan C. Krajewski; Brady R. Cunningham; William Bragg; Noelani R. Boise; Kristin D. Victry; David S. Wunschel; Karen L. Wahl; Elizabeth I. Hamelin (Harmful Algae, 2024)

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

The role of Dnmt1 in oocyte development - Emily A. Shelby; Elizabeth C. McKinney; Christopher B. Cunningham; Alvin M. Simmons; Allen J. Moore; Patricia J. Moore (Journal of Insect Physiology, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Gene expression underlying parenting and being parented shows limited plasticity in response to different ambient temperatures - Jeanette B. Moss; Christopher B. Cunningham; Elizabeth C. McKinney; Allen J. Moore (Molecular Ecology, 2022)
Flexible interactions between parents and offspring are essential for buffering families against variable, unpredictable, and challenging environmental conditions. In the subsocial carrion beetle, Nicrophorus orbicollis , mid‐summer temperatures impose steep fitness costs on parents and offspring but do not elicit behavioural plasticity in parents. Here, we ask if plasticity of gene expression underpins this behavioural stability or facilitates independent compensation by larvae. To test this, we characterized gene expression of parents and offspring before and during active parenting under benign (20°C) and stressful (24°C) temperatures to identify genes of parents and offspring associated with thermal response, parenting/being parented, and gene expression plasticity associated with behavioural stability of parental care. The main effects of thermal and social condition each shaped patterns of gene expression in females, males, and larvae. In addition, we implicated 79 genes in females as “buffering” parental behaviour across environments. The majority of these underwent significant changes in expression in actively parenting mothers at the benign temperature, but not at the stressful temperature. Our results suggest that neither genetic programmes for parenting nor their effects on offspring gene expression are fundamentally different under stressful conditions, and that behavioural stability is associated primarily with the maintenance of existing genetic programmes rather than replacement or supplementation. Thus, while selection for compensatory gene expression could expand the range of thermal conditions parents will tolerate, without expanding the toolkit of genes involved selection is unlikely to lead to adaptive changes of function.

Correction to: Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Drivers and physical processes of drought events over the State of São Paulo, Brazil - Abayomi A. Abatan; Simon F. B. Tett; Buwen Dong; Christopher Cunningham; Conrado M. Rudorff; Nicholas P. Klingaman; Rafael C. de Abreu (Climate Dynamics, 2022)
The State of São Paulo, Brazil (SSP) was impacted by severe water shortages during the intense austral summer drought of 2013/2014 and 2014/2015 (1415SD). This study seeks to understand the features and physical processes associated with these summer droughts in the context of other droughts over the region during 1961–2010. Thus, this study examines the spatio-temporal characteristics of anomalously low precipitation over SSP and the associated large-scale dynamics at seasonal timescales, using an observation-based dataset from the Climatic Research Unit (CRU) and model simulation outputs from the Met Office Hadley Centre Global Environment Model (HadGEM3-GA6 at N216 resolution). The study analyzes Historical and Natural simulations from the model to examine the role of human-induced climate forcing on droughts over SSP. Composites of large-scale fields associated with droughts are derived from ERA-20C and ERA-Interim reanalysis and the model simulations. HadGEM3-GA6 simulations capture the observed interannual variability of normalized precipitation anomalies over SSP, but with biases. Drought events over SSP are related to subsidence over the region. This is associated with reduced atmospheric moisture over the region as indicated by the analysis of the vertically integrated moisture flux convergence, which is dominated by reduced moisture flux convergence. The Historical simulations simulate the subsidence associated with droughts, but there are magnitude and location biases. The similarities between the circulation features of the severe 1415SD and other drought events over the region show that understanding of the dynamics of the past drought events over SSP could guide assessment of changes in risk of future droughts and improvements of model performance. The study highlights the merits and limitations of the HadGEM3-GA6 simulations. The model possesses the skills in simulating the large-scale atmospheric circulations modulating precipitation variability, leading to drought conditions over SSP.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Morphine and ethanol pretreatment effects on expression and extinction of ethanol-induced conditioned place preference and aversion in mice - Christopher L. Cunningham; Lee Bakner; Lindsey M. Schuette; Emily A. Young (Psychopharmacology, 2021)

Behavioral effects of benzylideneoxymorphone (BOM), a low efficacy µ opioid receptor agonist and a δ opioid receptor antagonist - Sanjana Mada; Lisa R. Gerak; Amélie Soyer; David R. Maguire; Zehua Hu; Vanessa Minervini; Christopher W. Cunningham; Charles P. France (Psychopharmacology, 2020)

Characterization of dry spells in Southeastern Brazil during the monsoon season - Christopher Cunningham (International Journal of Climatology, 2020)
Given the lack of studies about dry spells over Southeastern Brazil (SEB), the present study aims to characterize them considering their duration, geographical incidence, and association with rainfall. Uninterrupted sequences of no‐rain days were calculated using the high‐resolution (10 km) Multi‐Source Weighted‐Ensemble Precipitation data set (MSWEP; 1979–2016). The majority of dry spells (80%) last no more than 9 days and those remaining for 10 days or more are relatively rare (top 20%). January and February present a predisposition for the occurrence of dry spells, feature that is not observed in December. The life cycle of dry spells evolves in close association with the subseasonal rainfall tendency. When adding the perspective of dry spells, the effective peak of the monsoon season is December, the month with the highest rainfall rates and the lowest chances for dry spells. Afterward, dry spells modulate a progressive weakening of the rainy season until March, when a slight recovery may happen in the central northern portions of SEB. The relationship between dry spells and rainfall is not straightforward. For dry spells that are most common (up to 9 days), the most likely association is with negative monthly anomalies up to −1.0 SD . However, there are also significant chances of having dry spells associated with positive anomalies. Extreme long dry spells, but extremely rare as well, are unequivocally associated with negative anomalies. The geographic discrimination of dry spells evidences a dipole‐like feature, better seen in January and February, similar to the well‐known rainfall dipole. The north and northeast portions tend to be drier, more prone to the occurrence of dry spells, both short/frequent and long/infrequent. In the south and southwestern portions, dry spells tend to be shorter. The main result is the indication of a probable lessening in the rainy season, taking place between January and February that might affect a significant portion of SEB.

A native apex predator limits an invasive mesopredator and protects native prey: Tasmanian devils protecting bandicoots from cats - Calum X. Cunningham; Christopher N. Johnson; Menna E. Jones (Ecology Letters, 2020)
Apex predators can limit the abundance and behaviour of mesopredators, thereby reducing predation on smaller species. We know less about whether native apex predators are effective in suppressing invasive mesopredators, a major global driver of vertebrate extinctions. We use the severe disease‐induced decline of an apex predator, the Tasmanian devil, as a natural experiment to test whether devils limit abundance of invasive feral cats and in turn protect smaller native prey. Cat abundance was c . 58% higher where devils had declined, which in turn negatively affected a smaller native prey species. Devils had a stronger limiting effect on cats than on a native mesopredator, suggesting apex predators may have stronger suppressive effects on evolutionarily naive species than coevolved species. Our results highlight how disease in one species can affect the broader ecosystem. We show that apex predators not only regulate native species but can also confer resistance to the impacts of invasive populations. Apex predators could therefore be a powerful but underutilised tool to prevent biodiversity loss.

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Effects of multi-modal cues on conditioned place preference in C57BL/6J and DBA/2J mice - Christopher L. Cunningham; Chloe N. Shields (Psychopharmacology, 2018)

Naloxone effects on extinction of ethanol- and cocaine-induced conditioned place preference in mice - Laura Font; Christa A. Houck; Christopher L. Cunningham (Psychopharmacology, 2017)

Sterol Carrier Protein-2: Binding Protein for Endocannabinoids - Elizabeth Sabens Liedhegner; Caleb D. Vogt; Daniel S. Sem; Christopher W. Cunningham; Cecilia J. Hillard (Molecular Neurobiology, 2014)

Effects of acute withdrawal on ethanol-induced conditioned place preference in DBA/2J mice - Sarah E. Dreumont; Christopher L. Cunningham (Psychopharmacology, 2014)

Effects of dopamine receptor antagonists on the acquisition of ethanol-induced conditioned place preference in mice - Melanie M. Pina; Christopher L. Cunningham (Psychopharmacology, 2014)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Local and remote responses to opposite Ross Sea ice anomalies: a numerical experiment with the CPTEC/INPE AGCM - Christopher A. Cunningham; José Paulo Bonatti (Theoretical and Applied Climatology, 2011)

Involvement of the orexin/hypocretin system in ethanol conditioned place preference - Charlene M. Voorhees; Christopher L. Cunningham (Psychopharmacology, 2011)

Transcriptome Profiling of Selectively Bred Pacific Oyster Crassostrea gigas Families that Differ in Tolerance of Heat Shock - R. Paul Lang; Christopher J. Bayne; Mark D. Camara; Charles Cunningham; Matthew J. Jenny; Christopher J. Langdon (Marine Biotechnology, 2009)

Reference-dose place conditioning with ethanol in mice: empirical and theoretical analysis - Peter A. Groblewski; Laura S. Bax; Christopher L. Cunningham (Psychopharmacology, 2008)

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

Rapid induction of Pavlovian approach to an ethanol-paired visual cue in mice - Christopher L. Cunningham; Priya Patel (Psychopharmacology, 2007)

Role of test activity in ethanol-induced disruption of place preference expression in mice - Christina M. Gremel; Christopher L. Cunningham (Psychopharmacology, 2007)

Intraseasonal modes of variability affecting the South Atlantic Convergence Zone - Christopher Alexander Castro Cunningham; Iracema Fonseca De Albuquerque Cavalcanti (International Journal of Climatology, 2006)

Allopregnanolone does not influence ethanol-induced conditioned place preference in DBA/2J mice - Kara I. Gabriel; Christopher L. Cunningham; Deborah A. Finn (Psychopharmacology, 2004)

Apparatus bias and place conditioning with ethanol in mice - Christopher L. Cunningham; Nikole K. Ferree; MacKenzie A. Howard (Psychopharmacology, 2003)

Reduced ethanol-induced conditioned taste aversion and conditioned place preference in GIRK2 null mutant mice - Katherine G. Hill; Herminia Alva; Yuri A. Blednov; Christopher L. Cunningham (Psychopharmacology, 2003)

Distal and proximal pre-exposure to ethanol in the place conditioning task: tolerance to aversive effect, sensitization to activating effect, but no change in rewarding effect - Christopher L. Cunningham; Laura E. Tull; Kirsten E. Rindal; Paul J. Meyer (Psychopharmacology, 2002)

Cloning, sequencing, and analysis of expression of a second IL-1 β gene in rainbow trout (Oncorhynchus mykiss) - Olga Pleguezuelos; Jun Zou; Charlie Cunningham; Christopher J. Secombes (Immunogenetics, 2000)

Genetic differences in cocaine-induced conditioned place preference in mice depend on conditioning trial duration - Christopher L. Cunningham; Shelly D. Dickinson; Nicholas J. Grahame; Dobrina M. Okorn; Carrie S. McMullin (Psychopharmacology, 1999)

GABA A receptors modulate ethanol-induced conditioned place preference and taste aversion in mice - J. A. Chester; Christopher L. Cunningham (Psychopharmacology, 1999)

Extinction of ethanol-induced conditioned place preference and conditioned place aversion: effects of naloxone - Christopher L. Cunningham; Carly M. Henderson; Nancy M. Bormann (Psychopharmacology, 1998)

Flavor preference conditioning by oral self-administration of ethanol - Christopher L. Cunningham; Jill S. Niehus (Psychopharmacology, 1997)